A dynamic spatial model of agricultural price transmission: Evidence from the Niger millet market - Goundan, Anatole; Tankari, Mahamadou Roufahi (International Food Policy Research Institute, 2016)
Spatial interactions are essential drivers of price transmission mechanisms and may significantly affect any food’s policy outcomes. However, spatial aspects seem to be generally overlooked when analyzing price transmission. This paper attempts to fill this gap by highlighting the usefulness of spatial interaction and models for market integration analysis. A spatial dynamic panel datamodel is presented and applied to Niger’s millet market. Empirical results show that (1) the millet market is partly integrated, (2) locally traded commodities (millet and sorghum) are linked by a cross-commodity price transmission, (3) most imported cereals prices, which for Niger is maize and rice, did not affect the millet market, and (4) no cross-regions price transmissionoccurred for the millet market.